Sustainable water governance: An incremental approach towards a decentralised, hybrid water system - Faragher, Tamsin (Urban Water Management, 2019)
Cape Town is experiencing its worst drought in recorded history. Notwithstanding that the Western Cape has always been a water scarce region, it is this current drought that has brought home the area’s inherent vulnerability and highlighted the governance issues. The world wherein South Africa’s water governance was created is very different to the world we find ourselves in today. It is a world of uncertainty and unpredictability not contemplated in water governance comprised of legislation, policy, guidelines and practice. The current water governance constructs a conventional approach based upon predictability and certainty and is no longer appropriate to meet today’s new challenges. Consistent with this conventional approach, Cape Town’s municipal water supply is almost completely dependent upon surface water which makes it even more vulnerable to drought than if its supply was comprised of a variety of water supply options. With surface water sources fully exploited and storage opportunities within the urban edge limited alternative water supply options must be more seriously considered and the water governance reformed to accommodate its use. Water governance is the focus of reform because it is the framework for infrastructure planning and therefore controls the resultant system, infrastructure and management. This thesis interrogates the current water governance as the starting point before firstly discussing the proposed incremental approach towards a decentralised, hybrid system for water infrastructure and secondly, identifying specific areas where intervention is necessary for implementation.